Impact of Loughborough Intermittent Shuttle Test versus soccer match on physiological, biochemical and neuromuscular parameters - Magalhaes, J.; Rebelo, A.; Oliveira, E.; Silva, J. R.; Marques, F.; Ascensao, A. (European Journal of Applied Physiology, 2010)
The aim of the present study was to analyze the impact of Loughborough Intermittent Shuttle Test (LIST) versus soccer match on heart rate (HR), muscle damage, redox status, blood leukocytes and neuromuscular function throughout 72 h recovery. Sixteen male soccer players (21.3 ± 1.1 years; 175.0 ± 6.0 cm; 70.7 ± 6.3 kg) completed LIST and performed a soccer match separated by 2 weeks and data were collected before, 30 min, 24, 48 and 72 h after LIST and match. HR, plasma creatine kinase (CK) activity, myoglobin (Mb), uric acid (UA), protein sulfhydryls (-SH), malondialdehyde (MDA) contents, total antioxidant status (TAS), blood leukocyte counts, delayed onset muscle soreness, 20 m sprint and jump performances, and maximal isokinetic knee extension and flexion were analyzed. HR after LIST was significantly lower than after the match. Post-match TAS was lower and UA was higher than after LIST. Thirty minutes and 24 h after soccer MDA was higher and -SH was lower than after LIST (P < 0.05). LIST and soccer match induced elevation in total leukocytes and a reduction in lymphocytes at 30 min. This reduction in blood lymphocytes 30 min after match was lower than after LIST. In conclusion, the impact of both exercises did not differ regarding the observed muscle damage markers and some neuromuscular parameters, although soccer requires higher cardiac demand and induced higher changes on redox status, adenine nucleotide metabolism and on lymphocyte counts than LIST, which should be taken into account when using LIST to simulate a match to study these type of physiological and biochemical-related endpoints.